Verbs in the Early Speeches of Two Manipuri-Speaking Children - Devi, Ahanthem Romita; Singh, L. Iboyaima (Nepalese Linguistics, 2022)
The paper seeks to highlight how concepts of verbs in general and motion verbs in particular unfold in two Manipuri-speaking children within the age group of 3-5 years of age. The focus is on motion or action verbs because of the prevalence of such words in child directed speech at home as well as in the school environment. Child directed speeches usually consists of action verbs mainly to get them acquainted with the world around them and to develop them as a social being. This study looks into the emergence of verbs, particularly the motion verbs, and sets a prelude to further extensive study in this area. It is also to see how far Uziel-Karl’s (2001) presentation of Hebrew motion verbs works for Manipuri motion verbs.